Information systems engineering in responsible information systems : CAiSE Forum 2019, Rome, Italy, June 3-7, 2019, Proceedings /: CAiSE Forum 2019, Rome, Italy, June 3-7, 2019, Proceedings. ([2019]) - Unknown
No abstract available